Kajian Pola Sebaran dan Perubahan Tipologi Permukiman Desa Celuk – Sukawati Menggunakan Citra Satelit - Widiantara, I Putu Adi; Dwijendra, Ngakan Ketut Acwin (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
Celuk Village as an icon of the silver industry in Bali has experienced a significant development of spatial patterns. This is influenced by the geographical location of Celuk Village which is an area bordering the suburbs of the City of Denpasar. Because land reserves that can be occupied in the City of Denpasar are decreasing, this triggers physical development to spread towards the outskirts of the city, thus causing the phenomenon called urban sprawl. Due to the expansion of physical development, as well as changes in rural forms, it will certainly affect the form of settlements and changes in their urban patterns. This study uses a deductive-quantitative method through a case study approach. Geospatial data using satellite imagery from Google Earth is processed through ArcGIS software. The results showed that there were changes in traditional settlements due to the addition of new functions and population growth, as well as the presence of non-traditional buildings as a result of the expansion of the village area due to economic growth, diverse community backgrounds, and urban spatial expansion.